Geometrical interpretation of the solution of systems of algebraic linear equations (PädiUAQ, 2017)
This work is a didactic proposal for teaching the subject of linear equations and geometrical interpretation of the solution, which is part of the reticular plan in the area of engineering. This article describes two practices related to the subject in order to improve understanding of the same, through the construction of a polyhedron whose faces are associated with equations of planes, the student determines with respect to a coordinate system reference and then form a system of equations whose solution is interpreted and verified both in physical form and with the help of a computer program that plots equations planes. The first of these practices corresponds to the case of systems of equations that have unique solution and the second to the case of systems that have many solutions.